2018
DOI: 10.1111/1759-7714.12755
|View full text |Cite
|
Sign up to set email alerts
|

EGFR exon 20 insertion mutation in advanced thymic squamous cell carcinoma: Response to apatinib and clinical outcomes

Abstract: Thymic carcinoma (TC) is a rare malignant tumor of the mediastinum with occult onset, rapid development, and poor prognosis. Surgery is the main treatment for early TC, but the majority of patients are diagnosed at Masaoka‐Koga stage III or IV with local invasion or distant metastasis. Platinum and anthracyclines are currently considered key components of first‐line chemotherapy for advanced TC; however, there are no standard treatment plans for patients who are refractory to first‐line and further chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This case was reported by our team in 2018, and his previous treatment is detailed in Yudong et al 6 . Here, we provide a detailed report on the patient's follow‐up treatment.…”
Section: Case Reportmentioning
confidence: 73%
See 1 more Smart Citation
“…This case was reported by our team in 2018, and his previous treatment is detailed in Yudong et al 6 . Here, we provide a detailed report on the patient's follow‐up treatment.…”
Section: Case Reportmentioning
confidence: 73%
“…This case was reported by our team in 2018, and his previous treatment is detailed in Yudong et al 6 Here, we provide a detailed report on the patient's follow-up treatment. A 52-year-old Asian male with over 40-years history of smoking was diagnosed with Masaoka-Koga stage IVB thymic squamous cell carcinoma at a local hospital.…”
Section: Case Reportmentioning
confidence: 76%
“… 13 Advanced thymic squamous cell carcinoma patients with an EGFR exon 20 insertion mutation were reported to respond to apatinib, achieving a PFS of 10 months. 14 He et al 15 also reported that an advanced TC patient treated with apatinib after chemotherapy failure and multiple lung metastases achieved partial remission (PR) and PFS was 6.3 months. In a phase II study, 26 patients with advanced thymoma or TC were treated with gefitinib, with one patient achieving PR and 15 patients achieving stable disease; however, no patients achieved CR.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib is a highly selective TKI, which mainly competes with the ATP-binding site of VEGFR-2. The patient was unable to tolerate the toxicity associated with apatinib and by the 13th month disease progressed ( 43 ). After the first anti-angiogenic TKI failed, anlotinib was well tolerated, without obvious AEs and the patient achieved a PFS of over 23 months; therefore, further clinical investigation of anlotinib is warranted ( 42 ).…”
Section: Targeted Agents In Tetsmentioning
confidence: 99%